Approaches to Service Provision During the Construction Phase of Nuclear Power Plants Abroad - A. A. Salnikova; D. V. Gudemenko (Глобальная ядерная безопасность)
The paper considers geographical distribution of the countries embarking on the implementation of the first projects for the construction of a large-capacity NPP. The risks affecting the construction of nuclear power plants are presented, the analysis of possible consequences is carried out, in particular, an increase in the cost of building a nuclear power plant and an increase in the duration of its construction in novice countries that are starting to implement nuclear power plant construction projects for the first time, arising as a result of the realized risk. The measures resorted to by the novice countries for the successful implementation of the project and mitigation of risks are considered. The necessity of maintenance of NPP construction and timely preparation for its operation is considered, as well as the analysis of the approaches of the Russian operating organization to the provision of such services at the stage of NPP construction abroad is carried out, the weak competitiveness of the “architect-engineer” approach is discussed, the preference is the “technical customer” and “owner\\s engineer” approaches is provided.